From Hope to Hardship: Understanding the Impact of Hierarchies and Violence in Medicine - Ximena Cors Cepeda (University Library System, University of Pittsburgh, 2024)
This article is an experience piece reflecting on my journey through medical school rotations, highlighting the pervasive nature of workplace violence (WPV) and its impact on students' motivation and mental health. I discuss the high incidence of mistreatment and its correlation with burnout, imposter syndrome, and decreased academic performance among trainees. I emphasize the importance of recognizing and addressing subtle forms of WPV, including microaggressions and systemic issues, and advocate for proactive measures such as education, training, and fostering cultural change within healthcare institutions. Through reflecting on my experiences and observations, I aim to inspire systemic change and empower individuals to contribute to a healthier, more empathetic medical culture.